INTERAKSI SOSIAL ANAK JALANAN DI LAMPU MERAH DEPAN KANTOR GUBERNUR KOTA PEKANBARU - Fitri Yanti; Rosmawati Rosmawati; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to meet and clearly describe the picture of the characteristics and social interactions among the street kids around traffics light in front of governor’s office of Pekanbaru city. The subjects of this study were seven street children. This research method uses a qualitative approach to the type of descriptive research. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusions. Characteristics of street children at a red light in front of the city Gubernur office in Pekanbaru aged 8 to 14 years, the activities carried out on the streets mostly peddle newspapers and hawkers. Street children are still intensive meeting with family even though it doesn’t take long to get together and still have a fairly complete family. Patterns of social interaction among the street children with families which include cooperation, accommodation, assimilation and acculturation, competition, dan conflict has gone well in all aspects. Street children interact well with their families, there is no meaningful conflict or disagreement, the dominant aspect of social interaction with street children is the collaboration of street children in the family, assimilation and acculturation, competition, and opposition.Key Words: Characteristics, Social Interaction, Street Children